Strategic Management by Madrasah Principals in Addressing Technology Infrastructure Shortages in Elementary Madrasahs - Ridwan Nurhidayat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to determine how the strategic management process of the Madrasah Principal at MI Dukuh Parakanmangu. This study uses a qualitative case study method. Data were collected through interviews, observations and documentation. The results of this study are the strategic management implemented by the Madrasah Principal consists of three stages: 1) formulation: The Madrasah Principal has a vision of making MI Dukuh superior in the use of technology through improving teacher competency and collaboration with other institutions. While the mission of the Madrasah Principal of MI Dukuh Parakanmanngu is to improve teachers' abilities in the field of technology by means of training and establishing collaboration with external institutions. Internal factors, technological facilities are still very minimal (only one laptop and one Wi-Fi), without a computer laboratory. External factors also have not supported permanently due to limited funds from parents. The strategies implemented include training through KKG, KKMI, and OPM, as well as setting aside funds from BOS. The long-term goal is to build technological facilities gradually and have its own computer laboratory space. Implementation: The annual goal is to collaborate with external parties to provide internet access and computers. The school administration has begun using digital systems such as online reporting, WhatsApp groups, and digital textbooks. School Operational Assistance (BOS) funds are managed to support the procurement of technology facilities. The organizational structure also supports this strategy through teacher meetings that actively discuss solutions to technology infrastructure issues. Evaluation: The evaluation involves holding regular working meetings between the principal and teachers to assess the results of the strategy and formulate next steps.